A Pragmatic Stylistic Evaluation of the Electronic Qur’an Translation in Surat Fatir into Indonesian Language - Mirwan Akhmad Taufiq; Achmad Yani (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
This study aims to verify the authenticity of the two translations of the digital Qur’an into the Indonesian language, its suitability, and its translation comparison of two digital Qur’ans. The researcher relied on the qualitative descriptive approach by pragmatically translating the digital Quran. The primary source of this study is https://quran.kemenag.go.id/ and https://kalam.sindonews.com/quran. The study concluded that the two digital Qurans have a correct translation, but some translation errors must be noted and modified. The two digital Qurans did not have a certificate of correction from the Qur’an Correction Committee at the Ministry of Religious Affairs. They did not contain information to document the authenticity of the Quran texts, and the translation reference was referred to as a printed and published source. Digital matters may be deleted and hidden due to electricity, network, or device, so it must have relied on a printed Qur’an.